Cerebro-umbilical doppler ratio as a predictor of adverse perinatal outcome - Kamalarani, A. Esther; Victor, Sheba Rosette (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Intrauterine growth restriction (IUGR) is defined as a subnormal bodyweight or mass in utero. Fetal Doppler studies have been identified as one of the reliable and non-invasive methods of antepartum fetal surveillance in growth-restricted fetuses to detect hypoxemia and to plan timely delivery to precede acidemia. The aim of this study is to evaluate the screening efficacy of the pulsatility indices (PI) of the umbilical artery (UA) and middle cerebral artery (MCA) and the ratio of these two indices in predicting the adverse perinatal outcome in pregnancies complicated by IUGR. Methods: In this study patients were included after diagnosed to have fetal growth restriction clinically by a disparity of four weeks or more between symphysis-fundal height and gestational age and on the serial measurement of symphysis-fundal height after 30 weeks of gestation. Results: Out of 100 patients who fulfilled the criteria for the study, only 85 patients delivered. Out of them, only 16 women (18.8%) had a ratio of <1.08 which was considered abnormal and the rest of the women (81.2%) had a ratio >1.08 which was considered normal. The specificity for the Cerebro-umbilical ratio (<1.08) to predict adverse perinatal outcome was 96% whereas that for PI of umbilical A (>1.12) was 83% and that for the PI of middle cerebral A (<1.2) was 84%. However, the sensitivities for these indices were very low. Conclusions: The ratio of the pulsatility indices of the umbilical artery and middle cerebral artery is useful to predict the adverse perinatal outcome.